Exploring Intercultural Engagement: The Multifaceted Challenges Faced by International Students in Hungary - Anisa Trisha PABINGWIT (Revista de Știinţe Educaţiei)
Engagement is widely regarded as a fundamental concept for understanding academic achievement and student motivation in contemporary educational science. Moreover, student mobility has been identified as an effective approach to enhance engagement among international students. Despite the numerous challenges posed by a foreign environment, Eastern-European higher education has seen a sharp rise in international student enrolment, driven by advancements in education, internationalization, and attractive opportunities. Established by a government decree in 2013, the Stipendium Hungaricum scholarship has positioned Hungary as a top destination for international students seeking higher education. However, awareness and engagement with cultural diversity and the available resources for international students remained limited, often resulting in their needs being overlooked. Given this, research on the experiences of international students and their adaptation to cultural diversity in Hungary warrants significant attention. This study aims to explore the challenges faced by international students across various Hungarian universities. Data were collected from N=15 international doctoral students through semi-structured interviews and analysed using qualitative thematic analysis. While the participants had high English proficiency, their limited Hungarian language skills emerged as a significant challenge in daily life and academic engagement. The emerging themes encompass cultural differences, social environments, and varied personal experiences, specifically focusing on communication, cultural challenges like language barriers, opportunities for social interaction—or their absence—along with accommodation services, and health concerns. The study’s findings offer valuable insights for leaders and stakeholders, aiding them in addressing challenges and improving preparations for welcoming international students through both short- and long-term strategies.